Smart TPE Materials Based on Recycled Rubber Shred - Klaudia Toczek (MDPI AG, 2021)
Thermo-responsive shape memory materials were developed based on recycled ethylene-propylene-diene (EPDM) rubber shred and thermoplastic elastomers (TPE). Ethylene-1-octene TPEs (Engage 8180, 8411, 8452) with varying degrees of crystallinity and Mooney viscosity were used to prepare the composite materials. To avoid the deterioration of static mechanical properties after mixing recycled EPDM rubber shred (RS) with thermoplastic elastomers, they were partially cured using dicumyl peroxide. The peroxide curing was the most effective for a rubber shred/Engage 8180 blend, where the highest cure rate index (CRI), 1.88 dNm⋅min−1, was observed. The curing caused an approximately 4-fold increase of tensile strength (TS) values for EPDM rubber shred/thermoplastic elastomer blend to the level acceptable for the rubber industry compared with an uncured blend. The incorporation of EPDM rubber shred changed thermoplastic elastomers’ viscoelastic behavior, increasing the values of storage (G′) and loss (G″) modulus. The lowest viscosity of molten Engage 8411 during mixing led to higher compatibility of rubber shred RS/8411 blend, as confirmed by analysis of Cole-Cole plots and the blend morphology. All rubber shred RS/TPE blends showed the shape memory behavior. For the RS/Engage 8452 blend, the highest shape fixity (F) value (94%) was observed, while the shape recovery (RR) was 87%. Studies confirmed that the intelligent materials with shape memory effect could be obtained via selectively chosen thermoplastic elastomers; ethylene-1-octene as a binder for recycled EPDM. Prepared recycled TPE/rubber shred blends can be successfully reused due to their viscoelastic and mechanical properties. Therefore, such a concept can be potentially interesting for the rubber industry.